The prevalence of ultrasonographic abnormalities and histopathologic lesions is high in testes of yearling tropical hair rams. Issue 3 (11th March 2019) - Dascanio, John; Roberson, Jerry; Pfent, Catherine; Nahar, Vinayak K.; Arauz, Maziel; Alexander, Kerry; Roberts, Brian; Cope, D. Andrew; Bridger, Rhett; Botsko, Dana
Abstract: Ultrasonography is commonly used to examine testes as part of a breeding soundness examination in sheep, especially, in cases of infertility or when gross testicular abnormalities are present. A descriptive, prospective, prevalence study was conducted to characterize the ultrasonographic, histopathologic, and spermatozoal morphology abnormalities present in a group of yearling tropic hair rams on the island of St. Kitts. Hyperechoic and shadowing abnormalities increased over a 6 month study period. Hyperechoic abnormalities were present in one or both testes in 89% (25/28) of yearling rams and 71% (40/56) of testes at castration. Shadowing abnormalities were present in one or both testes in 46% (13/28) of rams and 34% (19/56) of testes at castration. Shadowing was present more with moderate and severe hyperechoic abnormalities, with few testes in the mild category having any shadowing. As hyperechoic and shadowing abnormalities increased in severity, so did the severity of microscopic lesions including increased interstitial cellularity/fibrosis, interstitial mineralization, seminiferous tubules mineralization (hyperechoic only), and chronic lymphoplasmacytic orchitis. There were no spermatozoal morphologic abnormalities other than an increase in distal cytoplasmic droplets. The study findings detail a pathologic event in this group of yearling rams that has an unknown etiology. Potential causes may include scrotal insulation, trauma, infectious causes, immunity alterations, nutritional imbalances, and ingestion of a toxin. Further studies are required to elucidate the causative agent.